Countdown Manipulatives: Accelerating the Subtraction Proficiency of the Grade Two Pupils - Berry, Rosenda Alicwas (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to improve the mastery of subtraction among Grade 2 pupils at Bahong Elementary School through the use of countdown manipulative materials: Take-off Visualization, Improvised Wheel Clock Count, and Sequential Ladder Count. Methodology: The respondents consisted of 32 Grade 2 pupils, and data were gathered using pretest and posttest questionnaires. Descriptive statistics and a t-test were used for data analysis. The results revealed that the pupils' mastery level in subtraction improved significantly after the intervention, with the overall posttest Mean Percentage Score (MPS) reaching 93.81%, which is described as